PENGARUH KOMUNIKASI, PENGAWASAN DAN KEAHLIAN TERHADAP KINERJA PEJABAT PEMBUAT KOMITMEN DALAM PROYEK APBN DI SUMATERA SELATAN PADA BALAI BESAR PELAKSANAAN JALAN NASIONAL III - Markoni Badri; H.M Aidil Fitri (Politeknik Negeri Sriwijaya, 2012)
The research is aimed to analyze the influence of Communication, Control, and Competence to the PPK Performance at the Big Hall of National Street Execution III in South Sumatra. There are two main problems in this research. Firrsly,are Communication, Control, and Competence simutenously influenced the PPK Performance at the Big Hall of National Street Execution III in South Sumatra, and secondly, are Communication, Control, and Competence partialy influenced the PPK Performance at the Big Hall of National Street Execution III in South Sumatra. The research mainly use primary data by delevering questionnaire to 114 selected respondens. SPSS Packaged is used to analyzed the data. The result showed that there are positively and significanly inluence either si,utenously or partialy among Communication, Control, and Competence to the PPK Performance at the Big Hall of National Street Execution III in South Sumatra,Implementation, become the input for the Big Hall of National Street Execution III in South Sumatra.